TRAINEE-TEACHERS' PERCEPTIONS ON TRADITIONAL, ONLINE AND HYBRID LEARNING MODES OF MATHEMATICS EDUCATION IN GHANA - Tsitsia, Bernice Yawa; Kabbah, Samuel Kwasi (African Journal of Education and Practice, 2020)
Purpose: The study examined trainee-teachers' perceptions on traditional, online and hybrid learning modes of Mathematics education. Methodology: Quantitative research design was employed. The public colleges of education students in Ghana were involved in the study. Purposive sampling technique was used in selecting the sample for the study. In all, data was collected on 315 levels 100 and 200 students. Descriptive data analysis was employed using the Jamovi Statistical Data Analysis (JSDA) tool. Findings: The results indicate with over 80% frequencies of students and above 4.0 means of choice of responses per variables, students are mostly comfortable interacting and communicating with their tutors and colleagues in face-to-face Mathematics learning environment. The results also confirmed, with about 60.9% and 76.2% frequencies respectively, the students' preferred Mathematics learning mode to be the blended teaching-learning and the face-to-face mode of assessments. Unique Contribution to Theory, Practice and Policy: With the advent of technologies and the prospects made in technology assisted instructions as revealed by literature, the Management and other stakeholders of the Colleges of Education are urged to facilitate Information Communication Technology (ICT) resources in their respective Colleges. This is to aid the implementation of the integration of face-to-face and the online teaching and learning of Mathematics courses.